2016
DOI: 10.1016/j.jnnfm.2016.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic settling of particles in shear flows of shear-thinning fluids

Abstract: General rightsThis document is made available in accordance with publisher policies. Please cite only the published version using the reference above. AbstractDynamic settling is the phenomenon whereby a relatively dense particle settles through a sheared flow of a non-Newtonian fluid at a speed that depends on the shear rate of the background flow. This means that due to the nonlinear rheology, the settling velocity may vary spatially and temporally as the background shear rate of the suspending fluid varies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Settling of suspensions in viscoplastic fluids can be categorized as static settling or dynamic settling, depending on the background flow conditions (quiescent in the former). It is well known in the oil industry that background shear enhances settling [15] in shear-thinning fluids. For viscoplastic fluids, Merkak et al [16] and Ovarlez et al [17] demonstrated shearinduced settling in fluids regardless of the yield number, showing that particles settle as soon as the fluid yield stress is overcome by macroscopic shear.…”
Section: Introductionmentioning
confidence: 99%
“…Settling of suspensions in viscoplastic fluids can be categorized as static settling or dynamic settling, depending on the background flow conditions (quiescent in the former). It is well known in the oil industry that background shear enhances settling [15] in shear-thinning fluids. For viscoplastic fluids, Merkak et al [16] and Ovarlez et al [17] demonstrated shearinduced settling in fluids regardless of the yield number, showing that particles settle as soon as the fluid yield stress is overcome by macroscopic shear.…”
Section: Introductionmentioning
confidence: 99%
“…An example of a numerical calculation of tailings deposition and sand segregation along a longitudinal beach cross-section is shown in Figure 4. Analytical linear theories for segregation in these open channels are provided by Sisson et al (2012) (1DV), Childs (2013) (2DV) and Childs et al (2016). Gelled bed formation is not contained in these analytical approaches.…”
Section: Figure 1 Changing Properties Of Sand-carrier Mixtures By Difmentioning
confidence: 99%
“…The static settling has been removed in our analysis. With reference to Chapter 5 of the PhD thesis by Childs (2013), the solution for the concentration distribution in the 2DV x-z plane is obtained by the mathematical method of characteristics, giving: Figure 6 shows the gross correspondence between the theories. There are, however, differences in the lower 20% of the flow.…”
Section: Analytical Theory 21 Analytical Segregation Modelmentioning
confidence: 99%
See 1 more Smart Citation